the Efevtivity of ABC Analysis Functional in Cognitive Restructuring to Overcome Academic Procrastination of Unesa Psychology Student - Mutiaranisa, Adelia Gita (Universitas Negeri Surabaya, 2023)
The aims of this study is to determine the efectivity of ABC functional analysis (Antecedent Behaviour Consequence) in cognitive restructuring for handling academic procrastination on Psychology student of Universitas Negeri Surabaya. This study is a quasi-experimental with one group pre-post test. This research is sample study. The subject are 33 A class Psychology students and 33 B class students. The instruments in this reasearch are PASS I, PASS II (Procrastination Assesment Scale-Students) and APSI (Academic Procrastinatin State Inventory). Otherwise questionnaire, in this research used self-report technique and Focus Group Discussion (FGD) too. Data analysis in this study used Paired sample T-test, and showed significance level for PASS I of A class is 0,433 and B class is 0,712, for PASS II of A class is 0,092 and B class is 0,774, and for APSI of A class is 0,916 and B class is 0,592. Because the score of significance p>0.05, showed that there was no significant changes for academic procrastination before and after ABC functional anaylisis in cognitive restructuring on Psychology students of Universitas Negeri Surabaya.